Blood pressure, antihypertensive medication and neuropsychiatric symptoms in older people with dementia: The COSMOS study. (8th October 2020) - de Jong‐Schmit, Bianca E. M.; Poortvliet, Rosalinde K. E.; Böhringer, Stefan; Bogaerts, Jonathan M. K.; Achterberg, Wilco P.; Husebo, Bettina S.
Abstract : Objectives: Neuropsychiatric symptoms (NPS) are very common in older patients with dementia. There is increasing evidence that hypoperfusion of the brain plays a role in the development of NPS. The aim of this study is to assess whether there is an association between low systolic blood pressure (SBP) and NPS and if NPS are more prevalent in older people with dementia using antihypertensive medication. Methods: We studied the baseline data from participants in the Co mmunication, S ystematic pain treatment, M edication review, O rganized activities and S afety study, a multicenter clustered trial with 765 participants from 72 nursing home units from 37 nursing homes in Norway. SBP (lowest quartile vs rest) and use of antihypertensive medication were predictors and Neuropsychiatric Inventory—Nursing Home version (NPI‐NH) score (total and clusters) was the outcome. Missing data were imputed, except for missing data in predictors. We used a mixed model analysis adjusted for age, sex and Minimal Mental State Examination (MMSE) score. In a sensitivity analysis, continuous SBP values were used. Results: In total, 412 patients were included with a mean age of 86.9 years, 53.9% had a MMSE score of <11. There was no difference in total NPI‐NH score between low and high SBP (difference −1.07, P dj = 0.62). There was no difference between high and low SBP and the NPI clusters. The use of antihypertensive medication was not associated with a different total or cluster NPI‐NH score compared to no use (difference −0.99, P adj = 0.95, P all = 0.37‐0.99, respectively). In the sensitivity analyses with the continuous SBP levels, there was no association between SBP and NPI‐NH score (estimate 1.00, 95%CI 0.98‐1.01, P = 0.25). Conclusion: We found no association between low SBP and NPS, nor between antihypertensive use and NPS.